Latent heat flux and air temperature anomalies along an active fault zone associated with recent Iran earthquakes - Alvan, Habibeh Valizadeh; Azad, Farid Haydari; Mansor, Shattri (Committee on Space Research, 2013)
Pre-earthquake physical and chemical interactions in the earth’s ground may cause anomalies in latent heat flux, air and surface temperature. Earthquakes occur when the energy accumulated in rocks releases. Sometimes, the movements of the ground cause ruptures in the earth’s surface and sometimes the two sides of an existing fault shift towards each other. In a structurally complex and inhomogeneous collision region such as the Iranian Plateau, seismicity is not the result of activity of a single fault but is due to energy discharge in fault zones hundreds of kilometers wide.